Menakar Urgensi Pendidikan Multikulturalis Masuk Kurikulum - Tumpal Daniel (STIT Muslim Asia Afrika, 2019)
Being aware of religious life and nation is inseparable, while the reality of Indonesian nation is very diverse in terms of tribe, religion, race and among groups (SARA). This condition is certainly potentially disrupt harmonization and harmony that led to conflict. Indonesian Muslims become the determinant factor of harmonization and religious harmony in Indonesia. This is because the majority of Muslims from the side of theology theologically bring the universal message of peace